An Analysis of the Effect of Marketing Mix Policy towards the Increase of Canned Meat Sales Volume in PT. Pelita Makmur Makassar - . Astati; . Nurwahidah (Jurnal Ilmu dan Teknologi Peternakan, 2013)
The aim of the research was to find out the effect of marketing mix policy towards the increase of canned meat sales volume at PT. Pelita Makmur Makassar. This research was carried out within two months, from March to April 2010 at PT. Pelita Makmur Makassar. Data were collected using observation and interview method. Data were analyzed using multiple regression analysis models. At 200 gram size, price and distribution significantly affected the sales of canned meat, while the product inventory and promotion did not significant affect the sales of canned meat. In the 340 gram size, product inventory and price significantly affected the sales of canned meat, while promotion and distribution had no significant effects on the sales of canned meat. In conclusion, product inventory, price, promotion, and distribution gives significant effect on sales of canned meat at PT. Pelita Makmur Makassar.